Correlation between Folic Acid and Homocysteine Plasma in Severe Pre-Eclampsia and Normal Pregnancy - Malahayati, Inke; Serudji, Joserizal; Sulastri, Delmi (Makara Journal of Health Research, 2018)
Background: Lack of folic acid intake or genetic abnormalities in folic acid metabolism was correlates with elevated plasma or serum homocysteine concentrations. This case-control analytical study aims to determine the correlation between folic acid and homocysteine levels in severe pre-eclampsia and normal pregnancy. Methods: We enrolled 46 pregnant women (age 20─35 years) with severe pre-eclampsia or normal pregnancy at a government hospital in Padang, Indonesia, between March and May 2015. The samples size was selected by consecutive sampling. Then, we determined folic acid and homocysteine levels using ELISA and statistical analysis using the independent t-test and Pearson correlation. Results: We observed a difference in folic acid levels between severe pre-eclampsia (39.48 ± 9.40 ng/mL) and normal pregnancy (47.04 ± 13.20 ng/mL, p < 0.05). A difference was also observed in homocysteine levels between pre-eclampsia (18.52 ± 0.41 pmol/mL) and normal pregnancy (17.80 ± 0.73 pmol/mL, p < 0.05). The correlation between folic acid and homocysteine in severe pre-eclampsia and normal pregnancy was negative (r =  -0.034, p > 0.05 and r  = -0.222, p > 0.05, respectively). Conclusions: Low folic acid levels tend to increase homocysteine levels in severe pre-eclampsia, whereas high folic acid levels tend to lower homocysteine levels in normal pregnancy.